Pemberian Insentif Terhadap Kepuasan Kerja Karyawan Satuan Non Vertikal Jaringan Pemanfaatan Air - Maria Kaok (Musamus Journal of Business & Management, 2020)
This study aims to analyze and measure the effect of providing incentives on employee job satisfaction, by taking the Implementation of certain Non-Vertical Work Units from the Papua Water Utilization Network in Papua - Merauke Province as the object of research. The population in this study amounted to 44 respondents and a sample of 44 respondents using nonprobability sampling or census sampling techniques. This research uses a quantitative approach with a simple regression analysis technique. Measurement of variables using a Likert scale and processed using SPSS version 22. The results of the calculation of the data using a simple regression analysis regarding the provision of incentives that affect employee job satisfaction Certain Non-Vertical Units Implementation of Papua Papua - Merauke Water Utilization Network, that the provision of incentives affects employee job satisfaction Specific Non Vertical Units Implementation of Papua Water Utilization Network Papua - Merauke Province, Judging from the results of the SPSS 22 output, the incentive variable (X) is obtained tcount = 4,589 while t-table = 1,682 and sig = 0,000 so Ha is accepted, because t-table <t-count. This means that the incentive independent variable (X) has a statistically positive and significant effect on the dependent variable of job satisfaction. Keywords: Incentives, Job Satisfaction